Previsão da mortalidade materna, neonatal e infantil a partir de indicadores de água e saneamento: um estudo com dados nacionais de 2016 - Caixeta, Nádia Camila Rodrigues Costa (2021)
Objective: To assess the association between maternal, neonatal, and child mortality and water and sanitation indicators, using 2016 national data on 215 countries. Methods: Retrospective, descriptive and ecological study based on information obtained from the World Bank websites, on the mortality rate and on the Environmental Performance Index website, on the indicators of drinking water and sanitation. Initially, descriptive analysis was performed and later a negative binomial regression model validated to estimate the association between mortality rates and water and sanitation indicators. Results: The analysis of the 2016 data set showed that sub-Saharan Africa is the region with the highest average maternal mortality rate (448 deaths per 100,000 live births), neonatal (26 deaths per 1,000 live births) and infants (69.6 deaths per 1,000 live births). The regions of Latin America, Asia, the Caribbean, the Middle East and North Africa, the Pacific and Sub-Saharan Africa have values far from meeting the target set for maternal mortality (70 deaths per 100,000 live births). For neonatal and infant mortality, the regions that have not yet reached the target of 12 deaths per 1,000 live births and 25 deaths per 1,000 live births, respectively, were Asia, the Pacific and sub-Saharan Africa. Negative binomial regression was able to predict and validate the great effect (R2 greater than 0.64) that the increase of houses with access to the sewage network, the increase in treated sewage and the reduction of the lack of access to drinking water, exerted on the reduction of mortality rates. Conclusion: The associations between mortality and the indicators of drinking water and sanitation suggest that there is synergy between them so that the improvement in the indicators of one SDS may result in the automatic improvement of the indicators of the other SDS which would save time and resources. It is expected that the statistical models studied can serve as tools to assist in the decision-making of managers and others interested in the fulfillment of the 2030 Agenda. Keywords: Water. Infant Mortality. Maternal Mortality. Early Neonatal Mortality. Sanitation.